2018
DOI: 10.1002/ird.2281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilization and sediment flow hydraulic characteristics on emitter clogging in muddy water drip fertigation system

Abstract: In a drip fertigation system using the Yellow River, suspended solids in the water serve as a bridge between physical flocculation and chemical adsorption. They impact the emitter clogging process and flow turbulence properties. Therefore, a laboratory test was conducted with artificial muddy water drip fertigation (MWF) to investigate the anti‐clogging performance of emitters. Four types of fertilizer (i.e. [CO (NH2)2], Ca (H2PO4)2·H2O, K2SO4 and [CO (NH2)2] + KH2PO4 + KNO3) were applied at 0.5, 1, 2 and 3% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…However, this threshold did not take the effect of fertilizer application into account. Suspended solids in the water may serve as a bridge between physical flocculation and chemical adsorption (Liu et al, 2018).…”
Section: ) Selection Of P Fertilizer Concentrationmentioning
confidence: 99%
“…However, this threshold did not take the effect of fertilizer application into account. Suspended solids in the water may serve as a bridge between physical flocculation and chemical adsorption (Liu et al, 2018).…”
Section: ) Selection Of P Fertilizer Concentrationmentioning
confidence: 99%
“…A mass of small particles of sediment settled in the posterior part of the drip irrigation pipe with a low flow velocity, and these particles entered the flow channel of the emitter with a high concentration. The deposited of small particles of sediment blocked the flow channel of the emitter, which caused a flow discharge decrease of the emitter (Liu et al 2018). With the increase of test times, the blockage degree of the emitter increased, resulting in a continuous increase of the clogged emitter quantity.…”
Section: Influence Of Commutative Flow Technology On Quantity Of Clog...mentioning
confidence: 99%
“…Most sediments (mainly silt particles) are deposited on both sides of the riverbed, where ecological problems such as soil desertification and sandstorms often occur [13,14]. Because the sand particle content is relatively high and the available water is low for the sediment, how to deal with the accumulated sediments remains a serious problem [15][16][17]. Previous studies have shown that sediment addition can change both the soil particle composition ratio and soil texture, thus changing the water and salt transport pattern of saline-sodic soil [18,19].…”
Section: Introductionmentioning
confidence: 99%